WIRELESS SENSOR NETWORK & ITS IMPORTANCE - Jyoti Sharma, Beerendra Kumar (International Journal of Research Science and Management, 2015)
The current technology is Wireless sensor Network which comprises of thousands of tiny, inexpensive, battery operated devices known as sensor node. These sensor nodes are pontentialy capable of capturing real time data , process and transmit it with high resolution to the base station. The real challenge for wireless sensor network is to design optimal routing protocol which enhance the network lifetime by reducing energy consumption. Energy saving is the main component in designing of network architecture. Here we compiled available information in comparison to new developed protocol with leach protocol using Network Simulator 2 (NS2). It proves the effectiveness of our proposed protocol in terms of higher packet delivery ratio, throughput, energy efficiency and network lifetime.